1993
DOI: 10.1172/jci116469
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronate activation of CD44 induces insulin-like growth factor-1 expression by a tumor necrosis factor-alpha-dependent mechanism in murine macrophages.

Abstract: in the presence of anti-TNFa antiserum. In addition, I-1,6 was found to exert a regulatory role on IGF-1 production by enhancing the TNFa effect. IL-1i/ and TNFa mRNA transcript expression as well as IGF-1 protein synthesis were also stimulated by chrysotile asbestos. Anti-CD44 antibodies had no effect whereas anti-TNFa antiserum blocked asbestosstimulated IGF-1 production. These results indicate that hyaluronate activation of CD44 induces cytokine expression and macrophage-derived IGF-1 production is dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
189
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(203 citation statements)
references
References 60 publications
10
189
1
3
Order By: Relevance
“…29 Some tumor cells express 24,25 and secrete 7 high amounts of HA. Ligation of CD44 on monocytes by HA induces release of IL-1 and TNF, 30,31 which is in keeping with the present findings that exposure of monocytes to HA induced significant production of ROIs. The latter was inhibited when monocytes were preincubated with anti-CD44 (but not anti-CD18 or anti-CD29) MAbs.…”
Section: Discussionsupporting
confidence: 92%
“…29 Some tumor cells express 24,25 and secrete 7 high amounts of HA. Ligation of CD44 on monocytes by HA induces release of IL-1 and TNF, 30,31 which is in keeping with the present findings that exposure of monocytes to HA induced significant production of ROIs. The latter was inhibited when monocytes were preincubated with anti-CD44 (but not anti-CD18 or anti-CD29) MAbs.…”
Section: Discussionsupporting
confidence: 92%
“…A direct effect of HYA on central mechanisms in cell activation is supported by the observation that soluble HYA stimulates IL 1-␤, TNF-␣, and insulinlike growth factor-1 (IGF-1) mRNA transcript expression as well as IGF-1 protein synthesis, Monoclonal antibodies to the HYA-receptor CD44 blocked the effects of HYA on IL-1-␤, TNF-␣ and IGF-1 expression [50]. There is also evidence that CD44 receptors function as matrix-organizing, matrix-anchoring HYA-binding proteins [51].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies strongly suggest that macrophages are a major extrahepatic source of IGF-1. 21,[36][37][38] In an animal injury model, Lu et al 36 found that macrophages of the Ly-6C(-) subtype accumulated in damaged muscle and produced a high level of IGF-1 to promote muscle regeneration. In a human study, IGF-1 has been implicated in the pathogenesis of idiopathic pulmonary fibrosis, and interstitial macrophages were identified as a source of IGF-1.…”
Section: Discussionmentioning
confidence: 99%